Atomic absorption spectrophotometric determination of selected elements in ferromanganese nodules from the Pacific, Atlantic, and Indian Oceans - Iskowitz, J M; Lee, John Jong-Hae; Zeitlin, Harry; Fernando, Quintus (PANGAEA, 2022)
Twenty-one samples of deep-sea ferromanganese nodules collected from the Pacific, Atlantic, and Indian oceans were supplied by the Lamont-Doherty Geological Observatory of Columbia University and the Hawaii Institute of Geophysics, University of Hawaii. The air-dried manganese nodules were crushed with the aid of a ceramic mortar and pestle, and sorted according to particle size using a set of U.S. standard mesh sieves. Powdered nodules (100/150 ?m) in particle diameter) were dried overnight at 450°C in a Lindberg furnace, and the weight loss of the sample was measured for H2O concentration determination. Exactly 500 mg of the dehydrated samples were acid-digested in a pressurized Teflon bomb and the contents were diluted to 100 ml with 0.5 M boric acid solution. Five replicates of each nodule specimen were digested and stored in polyethylene bottle. Four aliquots of the acid-digested sample were pipetted into separate beakers to which aqueous thallium standards were added successively with Eppendorf micropipettes. Each sample solution was adjusted to pH 10.8, and the wash solution was added to the separatory funnel. Five milliliters of a 1% APDC solution and 10 ml of MIBK were pipetted into each separatory funnel. The funnels were mounted on a Kraft Model S-500 mechanical shaker and shaken at a maximum amplitude for 10 min. A Perkin-EImer 603 atomic absorption spectrophotometer equipped with Westinghouse single-element hollow cathode lamps was used together with an air-acetylene oxidizing flame and a 10-cm single slot burner for all the measurements. Thallium was determined in the APDC-MIBK extract as soon as possible after the extraction step was completed, using the primary wavelength (276.8 nm), a 16 mA lamp current, and a slit setting at 4. Other metals such as Mn, Fe, Cu, Ni, and Co were measured directly in a portion of the acid-digested samples without carrying out the solvent extraction preconcentration step.
Keywords: Geochemistry; manganese micronodule; manganese nodule; ocean; sediment